Pembangunan Dashboard Lokasi Rawan Tanah Longsor di Indonesia Menggunakan Tableau - Ridho Darman (Maranatha University Press, 2018)
Indonesia's geographical location is encountered by three major plates of the world causing the land of Indonesia is prone to landslide disaster. A landslide disaster can cause material and immaterial damage. The National Board for Disaster Countermeasure (BNPB) is an institution that has data on the disaster in large size including landslide natural disaster. So that the data can be processed into information more valuable, it required an application that can visualize the data so that it can display information in the form of disaster-prone areas and safe from disaster, especially landslides. The implementation of business intelligence is very suitable for this case so that BNPB can classify the disaster, especially landslide in every territory in Indonesia to facilitate the public get information about landslide disaster that happened and can become a reference in disaster mitigation preparedness. This research uses one of business intelligence software that is Tableau to show visualization in the form of a dashboard about landslide disaster that happened in Indonesia.